Particulate matter from tobacco versus diesel car exhaust: an educational perspective. Issue 3 (25th August 2004) - Invernizzi, G; Ruprecht, A; Mazza, R; Rossetti, E; Sasco, A; Nardini, S; Boffi, R
Abstract : Background: Air pollution is a common alibi used by adolescents taking up smoking and by smokers uncertain about quitting. However, environmental tobacco smoke (ETS) causes fine particulate matter (PM) indoor pollution exceeding outdoor limits, while new engines and fuels have reduced particulate emissions by cars. Data comparing PM emission from ETS and a recently released diesel car are presented. Methods: A 60 m 3 garage was chosen to assess PM emission from three smouldering cigarettes (lit sequentially for 30 minutes) and from a TDCi 2000cc, idling for 30 minutes. Results: Particulate was measured with a portable analyser with readings every two minutes. Background PM10, PM2.5, and PM1 levels (mean (SD)) were 15 (1), 13 (0.7), and 7 (0.6) μg/m 3 in the car experiment and 36 (2), 28 (1), and 14 (0.8) μg/m 3 in the ETS experiment, respectively. Mean (SD) PM recorded in the first hour after starting the engine were 44 (9), 31 (5), and 13 (1) μg/m 3, while mean PM in the first hour after lighting cigarettes were 343 (192), 319 (178), and 168 (92) μg/m 3 for PM10, PM2.5, and PM1, respectively (p < 0.001, background corrected). Conclusions: ETS is a major source of PM pollution, contributing to indoor PM concentrations up to 10-fold those emitted from an idling ecodiesel engine. Besides its educational usefulness, this knowledge should also be considered from an ecological perspective.